Adhesion enhancement and damage protection for carbon fiber-reinforced polymer (CFRP) composites via silica particle coating. (June 2018) - Kim, Kyungtae; Jung, Yong Chae; Kim, Seong Yun; Yang, B.J.; Kim, Jaewoo
Graphical abstract: Abstract: Adhesive materials for carbon fiber reinforced polymer (CFRP) composites have attracted the interest of researchers as an effective means to bond newly developed lightweight and high-performance composite structures. In this study, we developed a novel method to overcome these critical problems through a silica particle coating. Four-step bonding procedures were proposed to bind heterogeneous materials, where various concentrations of silica particles were introduced to coat CFRP composite surfaces uniformly in order to serve as a reinforcement and as a protection barrier layer against CFRP fractures. Experimental evaluations of the mechanics and fractography studies were conducted to clarify the correlations among the silica concentrations, adhesive strength levels, coating properties, and CFRP surface fractures. It was demonstrated that the introduction of the silica surface coating improves the adhesive strength by approximately 20% while also reducing CFRP surface fractures significantly by around 90%.